Sex differences in growth performance are related to cecal microbiota in chicken. (January 2021) - Cui, Lei; Zhang, Xiaolong; Cheng, Ranran; Ansari, Abdur Rahman; Elokil, Abdelmotaleb A.; Hu, Yafang; Chen, Yan; Nafady, Abdallah A.; Liu, Huazhen
Abstract: In poultry industry, male chickens have a better growth performance than female ones under the same genetic background and diet. Emerging evidences proposed an important role of intestinal microbiota in chicken's growth performance. This study aimed to determine gut microbiota related gender based differences in the growth performance of chickens. Therefore, male and female chickens (n = 20) at 7-week age were used to carry out histomorphological, molecular, gene expression analysis with their liver, chest and leg muscle, as well as 16S rRNA sequencing analysis for gut microbiota. The results revealed that Bacteroides and Megamonas genera were more prominently colonized in the cecum of male chickens. The male chicken's cecal microbiota indicated a closer relation with glycan metabolism, while in the female chickens it was more related with lipid metabolism. Gene expression levels associated with glycan and lipid metabolism were different between male and female chickens. Further, using Spearman correlation analysis, we found a positive correlation between glycan and lipid metabolism, and the relative abundance of Bacteroides, Megamona and Lactobacillus in male chickens. Similarly, we also found a positive correlation between the lipid metabolism and the relative abundance of Ruminococcaceae and Enterococcus in female chickens. These findings revealed the association of chicken growth performance with cecal microbiota that contributed to the metabolism of glycan and lipid in a sex-dependent manner. Highlights: A significant difference was observed in growth performance between male and female chickens. Cecal microbiota significantly participated in glycan and lipid metabolism. There might be a novel interaction in the mechanisms of probiotic and microbiome-host for poultry production.